Whiteness as futurity and globalization of higher education - Shahjahan, Riyad A.; Edwards, Kirsten T. (Higher education, 2022)
Amid growing debates about globalization of higher education (HE) reproducing inequalities, an analysis of race as the organizing influence underlying this global phenomenon remains absent. This conceptual essay argues that our understanding of globalization of HE would benefit from an intersectional understanding of critical Whiteness studies and temporal studies to help racialize and further temporalize this phenomenon. It introduces Whiteness as futurity framework and its three components: Whiteness as (a) aspiration, (b) investment, and (c) malleability. Drawing on this framework, it provides a critical race temporal account of globalization of HE by critically examining two contemporary global HE trends, namely: (a) the global diffusion of liberal education, and (b) the growing use of global university rankings (GURs). It argues that Whiteness as futurity colonizes (or orients) global subjects’ (nation-states’, policy makers’, institutions’, and individuals’) imaginaries and reinforces the asymmetrical movements, networks, and untethered economies underpinning global HE. The article concludes that educators should consider seriously the insights of Whiteness studies in reconceptualizing globalization of HE.